2016
DOI: 10.1111/are.13204
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Antioxidant characteristics of Persian sturgeon (Acipenser persicus) seminal plasma did not show significant changes duringin vitrostorage (48 h at 4°C)

Abstract: The below article, published online on Wiley Online Library (http://wileyonlinelibrary.com) has been retracted by agreement between the submitting author, Mohammad Sadegh Aramli, the Editors, Ronald Hardy, Lindsay Ross, Shi‐Yen Shiau, Marc Verdegem, and John Wiley & Sons Ltd. After a thorough investigation, there is strong evidence to indicate that the peer review of this paper was compromised. The identities of the reviewers were unable to be verified and it is believed that the paper was accepted based on re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The oxidative damage observed in the present study suggests a inefficiency in the neutralization of ROS by the antioxidant defenses, since even with the increase of antioxidant enzyme activity, such as SOD, sperm presented high levels of lipoperoxidation and DNA damage. Aramli and Kalbassi (2016) also showed that the increase of the antioxidant defenses in the species Acipenser persicus was accompanied by the increase of oxidative damages. Fish sperm have characteristics that make them susceptible to damage related to oxidative stress, considering the high amount of polyunsaturated fatty acids of sperm membrane ( Shaliutina et al, 2013 ).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The oxidative damage observed in the present study suggests a inefficiency in the neutralization of ROS by the antioxidant defenses, since even with the increase of antioxidant enzyme activity, such as SOD, sperm presented high levels of lipoperoxidation and DNA damage. Aramli and Kalbassi (2016) also showed that the increase of the antioxidant defenses in the species Acipenser persicus was accompanied by the increase of oxidative damages. Fish sperm have characteristics that make them susceptible to damage related to oxidative stress, considering the high amount of polyunsaturated fatty acids of sperm membrane ( Shaliutina et al, 2013 ).…”
Section: Discussionmentioning
confidence: 92%
“…Oxidative stress can induce metabolic disorders that reduce sperm motility. As suggested by Aramli and Kalbassi (2016) , oxidative stress causes disturbances in the sperm metabolism, which results in decreased sperm motility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation